The Contribution of ESG Information to the Financial Stability of European Banks - Tóth, Balázs; Lippai-Makra, Edit; Szládek, Dániel; Kis, Gábor Dávid (Public Finance Quarterly, 2021)
Nowadays more and more economic actors publish information regarding sustainability, through economic (E), social (S), and governance (G) performance. In the case of banks, ESG performance is important as they affect most of the industries through their investments and loans. In this research our aim is to investigate the relationship between financial stability and ESG performance. We applied panel regressive methods during the analysis. The sample consisted of stock exchange listed lending institutions (243 banks) from the European Union (EU) and the European Free Trade Association (EFTA). Our results show that ESG performance reduced the ratio of non-performing loans significantly. Furthermore, the positive effect of regulatory capital has been confirmed. Consequently, we can assert that the economic, social, and governance performance have beneficial impacts on financial stability. Therefore, the consideration of these pieces of information should be important for the investors and the regulators as well.